In the context of aneurysmal subarachnoid haemorrhage (aSAH), increased level of serum inflammatory markers is associated with a higher modified fisher score and a worse WFNS and hunt and hess score - Mpanza, Morena Nthuse (My University, 2020)
AIM To evaluate the relationship between Inflammatory Biomarker Levels and the Modified Fisher Score in patients with Spontaneous Subarachnoid Haemorrhage at the Johannesburg Academic Hospitals. METHOD This was a prospective, descriptive cross-sectional three-centre study involving patients with aneurysmal subarachnoid haemorrhage (aSAH) diagnosed on CT and CTA scans. The patients had blood samples taken in order to measure the levels of serum inflammatory biomarker CRP (and others), and test whether there was a relationship between biomarker levels and the amount of aneurysmal bleed as determined by the Modified Fisher Score on initial CT scan, as well as the clinical grading scores (Hunt and Hess and WFNS). When all inclusion criteria were met their records were reviewed and data pertinent to the study was extracted for statistical analysis. RESULT A Total of 67 patients were screened, of which only 49 met the inclusion criteria. Their ages ranged from 18 to 77 with a mean of 50 (SD +/- 15,2 years). More females were affected than males (65 vs 35%). Blacks made up 88% of the study population, Caucasians 8% and Indians 4%. Risk factors (hypertension, smoking and family history of stroke) were probed and, although having no statistically significant relationship with aSAH grading systems, there was a trend. Clinical presentation of aSAH (sentinel headache, seizures) in this study was consistent with findings in literature. More than half of the study population presented with moderate to severe aSAH assessed by clinical (Hunt and Hess, and WFNS) and radiological (Modified Fisher) Scores. The death rate was 14,3% - with an average time of 3 days from admission to demise. Hydrocephalus was present in 51% of the study population as a whole and also showed higher presence in those with more severe scores clinically and radiologically. Aneurysm characteristics (location, laterality and size) revealed a total of 59 singular aneurysms from which 11 locations were derived – the most common of which were located on the ICA (29%), MCA (23%), ACoA (22%) and ACA (19%). Aneurysm location and size did not show any preponderance for aSAH severity in this study. The biomarkers considered for the current study, and in particular CRP, largely proved to have a non-significant relationship with the Hunt and Hess, WFNS and Modified Fisher Scores. Albumin at Day 0 showed a significant relationship to the Modified Fisher Score; while ESR and platelets at Day 0 correlated to the Day 0 Hunt and Hess Score; and ESR at Day 0 correlated to Day 0 WFNS. CONCLUSION There was insufficient evidence in the current study to prove that a relationship existed between the level of serum inflammatory markers and the Modified Fisher, Hunt and Hess and WFNS Scores. Challenges with data collection, referral protocols and patient education may have influenced the final outcomes.
A research report submitted in partial fulfilment of the requirements for the degree Master of Medicine in Neurosurgery to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020